Decreased occurrence of ketoacidosis and preservation of beta cell function in relatives screened and monitored for type 1 diabetes in Australia and New Zealand. Issue 8 (7th October 2022) - Wentworth, John M.; Oakey, Helena; Craig, Maria E.; Couper, Jennifer J.; Cameron, Fergus J.; Davis, Elizabeth A.; Lafferty, Antony R.; Harris, Mark; Wheeler, Benjamin J.; Jefferies, Craig; Colman, Peter G.; Harrison, Leonard C.
Abstract: Aims: Islet autoantibody screening of infants and young children in the Northern Hemisphere, together with semi‐annual metabolic monitoring, is associated with a lower risk of ketoacidosis (DKA) and improved glucose control after diagnosis of clinical (stage 3) type 1 diabetes (T1D). We aimed to determine if similar benefits applied to older Australians and New Zealanders monitored less rigorously. Methods: DKA occurrence and metabolic control were compared between T1D relatives screened and monitored for T1D and unscreened individuals diagnosed in the general population, ascertained from the Australasian Diabetes Data Network. Results: Between 2005 and 2019, 17, 105 relatives (mean (SD) age 15.7 (10.8) years; 52% female) were screened for autoantibodies against insulin, glutamic acid decarboxylase, and insulinoma‐associated protein 2. Of these, 652 screened positive to a single and 306 to multiple autoantibody specificities, of whom 201 and 215, respectively, underwent metabolic monitoring. Of 178 relatives diagnosed with stage 3 T1D, 9 (5%) had DKA, 7 of whom had not undertaken metabolic monitoring. The frequency of DKA in the general population was 31%. After correction for age, sex and T1D family history, the frequency of DKA in screened relatives was >80% lower than in the general population. HbA1c and insulin requirements following diagnosis were also lower in screened relatives, consistent with greater beta cell reserve. Conclusions: T1D autoantibody screening and metabolic monitoring of older children and young adults in Australia and New Zealand, by enabling pre‐clinical diagnosis when beta cell reserve is greater, confers protection from DKA. These clinical benefits support ongoing efforts to increase screening activity in the region and should facilitate the application of emerging immunotherapies.